Language and silence in Lewis Nkosi’s novel Mating Birds - Maceri, María Ximena (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The present paper proposes an examination of instances from Lewis Nkosi’s novel Mating Birds (1983), in order to show how the text exposes racism under apartheid through the balanced use of language and silences. Firstly, there is an exploration of issues concerning the relationship between society and apartheid from a historical perspective – this is crucial to understand how space becomes relevant in the configuration of the narrative. Secondly, the analysis focuses on two questions: a) how the English language created a hybrid protagonist whose lack of belonging is the ultimate consequence of apartheid; and, b) how meaningful silence is for the interpretation of the novel. In the interaction that takes place among the uses of language and silence, social space and apartheid policies the author revives features of the South African oral tradition in a narrative that combines future, present and past in “an ever-unfolding now” (Edwards, 2008, 41).